Implementing Blockchain in Media Management Systems to Ensure Content Authenticity and Copyright Protection - I Gede Agus Krisna Warmayana (Yayasan Adra Karima Hubbi, 2024)
Background. Blockchain technology has gained widespread attention recently due to its potential to improve transparency, security, and efficiency in various sectors. In the media industry, content authenticity and copyright protection issues are often significant challenges. Blockchain technology offers potential solutions to ensure the authenticity of content and protect copyrights through a decentralized and immutable system. Purpose. This study aims to explore the implementation of blockchain technology in media management systems to ensure content authenticity and copyright protection. This research focuses on how blockchain can create a transparent and secure record of every transaction and change related to media content. Method. This research uses a qualitative approach with a case study method. The data was collected through in-depth interviews with blockchain technology experts, media professionals, and copyright lawyers. Analysis of documents and literature was also carried out to support the findings. Thematic analysis techniques identify key themes and patterns in the collected data. Results. The results show that implementing blockchain technology in media management systems can significantly improve content authenticity and copyright protection. Blockchain allows the creation of transparent records of ownership and changes in content, which are difficult to forge. This helps trace the content’s origin and ensures that copyrights are respected and protected. Conclusion. The research concludes that blockchain technology has great potential to address content authenticity and copyright protection challenges in the media industry. Blockchain implementation can create a more transparent and secure media management system, increasing trust between content creators, distributors, and consumers. The research recommends further development and trial of blockchain implementation in various media contexts to explore the full potential of this technology.